Effect of Learning Motivation on Learning Outcomes of Physical Education Sports and Health (Penjasorkes) - Deffri Anggara; Dolly Apriansyah (Perkumpulan Dosen Muda Bengkulu, 2023)
The purpose of this study was to find out the Learning Motivation on the Learning Outcomes of Physical Education Sports and Health (Penjasorkes) at SMP Negeri 2 Ujan Mas. Based on the problems and research objectives, the method used in this study is a quantitative method using a correlation approach, namely using a structural equation that looks at the causality of the dimensions of the influence of Learning Motivation (X1) on Physical Education Learning Outcomes (Y) Data on student motivation at SMP Negeri 2 Ujan Mas obtained from samples (respondents) from SMP Negeri 2 Ujan Mas, with a total of 76 students. The statement items on the learning motivation variable are 30 items, the score ranges from 1-5, where the highest score is 150, and the lowest score is 30. Based on the results of research on learning motivation, the average = 114.67 and the standard deviation is 12.05. While the highest score = 145 and the lowest score = 77. Description of the data on students' learning motivation at SMP Negeri 2 Ujan Mas can be seen in Table 1 as follows. Based on the results of the second semester exam for the Physical Education subject, the Physical Education learning outcomes of the students who were sampled in this study totaled 76 students, arranged in the frequency distribution table, the number of class intervals was 8 class intervals with a class length of 4.02. The average value of the physical education learning outcomes data is 79.26, the standard deviation is 4.75, the highest value is 90, and the lowest value is 60. The results of data processing in the frequency distribution are presented in the following table.